General Energy Decay Study for Memory Type Timoshenko System with Thermoelasticity Type III with Memory Damping Terms - Bellal, Nabila; Messikh, Chahrazed; Bouraoui, Hamed A.; Djebabla, Abdelhak (Journal of Applied Nonlinear Dynamics, 2026)
In this work, we consider a one-dimensional thermoelastic system of the Timoshenko type which was studied by Ghennam and Djebabla. Replacing their boundary conditions by the Dirichlet-Neumann conditions, we prove that the system decays in a general way independently of the system’s coefficients which constitutes an improvement of the above-mentioned work. Finally, we provide some numerical results to validate the theoretical results.